2018
DOI: 10.1158/1078-0432.ccr-17-3119
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 Inhibitor FIT-039 Suppresses Viral Oncogenes E6 and E7 and Has a Therapeutic Effect on HPV-Induced Neoplasia

Abstract: Cervical cancer is one of the leading causes of cancer-related deaths among women worldwide. The purpose of this study is to assess the therapeutic effect of the newly developed cyclin-dependent kinase 9 (CDK9) inhibitor FIT-039 on cervical neoplasia induced by human papillomavirus (HPV) infection. We examined FIT-039 for its effect on HPV gene expression in HPV cervical cancer cells. Primary keratinocytes monolayer and organotypic raft culture models were used to evaluate HPV viral replication and cervical in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Several viral proteins regulate P-TEFb (31,54). Recently, it was reported that the CDK9 inhibitor FIT-39 repressed HPV early promoter activity, resulting in reduction of E6 and E7 transcripts (36). From our experiments, we presume that both WT E2 and Y138F can compete with CDK9 for Brd4-CTD binding more favorably than Y138E, and we subsequently tested Y138E and Y138F for transcriptional activation.…”
Section: Discussionmentioning
confidence: 69%
“…Several viral proteins regulate P-TEFb (31,54). Recently, it was reported that the CDK9 inhibitor FIT-39 repressed HPV early promoter activity, resulting in reduction of E6 and E7 transcripts (36). From our experiments, we presume that both WT E2 and Y138F can compete with CDK9 for Brd4-CTD binding more favorably than Y138E, and we subsequently tested Y138E and Y138F for transcriptional activation.…”
Section: Discussionmentioning
confidence: 69%
“…Although there exists continuous research concerning the tumorigenesis and development of endometrial cancer, it still remains unclear which signaling pathways or related molecules promote the occurrence and development of endometrial cancer. Many studies confirm that overexpression of cyclin-dependent kinase 9 (CDK9) is directly related to tumor development ( 13 19 ). A recent study found that CDK9 inhibition dephosphorylates the SWI/SNF protein BRG1 (ATP-dependent helicase) and reactivates epigenetic silenced genes in cancer, thereby restoring tumor-suppressor gene expression ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDK9 expression is significantly increased in different cellular processes and different tissues, and has an important contribution to the progression of various types of cancer (10). Recently, studies have found that CDK9 is of critical importance in the development of many cancers, including Targeting CDK9: A novel biomarker in the treatment of endometrial cancer leukemia, cervical cancer, prostate cancer, glioblastoma, breast cancer, melanoma and lung cancer (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the CTD is phosphorylated by CDK7 on Ser 5 (s5) during transcription initiation and then on Ser 2 (s2) by CDK9 to promote transcriptional elongation (18). Recently, CDK9 has been shown to play crucial roles in many types of human cancer, including leukemia, cervical cancer, prostate cancer, glioblastoma, breast cancer, melanoma, and lung cancer (19)(20)(21)(22)(23)(24)(25). However, the relationship between CDK9 expression and clinical prognosis and the therapeutic potential of targeting CDK9 in ovarian cancer remains unclear.…”
mentioning
confidence: 99%